Intervention measures for stigma in HIV patients: a scoping review of randomized controlled trials - Zhang, Mingrui; Zhu, Hongxu; Xu, Yi; Li, Xiahui; Yang, Kaihan; Niu, Bei; Wang, Xue (Frontiers in Public Health, 2025)
BackgroundIndividuals infected with HIV experience significant stigma, and since this stigma can severely impact their quality of life, it is essential to implement interventions aimed at reducing the stigma faced by this population.ObjectiveTo summarize and analyze the core components and effectiveness of interventions targeting stigma among people living with HIV. Methods A scoping review methodology was employed to search the PubMed, Web of Science, Embase, Cochrane, and Scopus databases from their inception dates up to March 14, 2025. The included studies were categorized and analyzed.ResultsA total of 39 articles were included in this review. Interventions addressing HIV-related stigma were conducted among various populations including pregnant women, older adults, adolescents, and sexual minority groups. Intervention contents included cognitive behavioral therapy, motivational interviewing, information-motivation-behavioral skills intervention, among others. There was significant variation in the frequency and duration of stigma interventions. Outcome measures used across studies included internalized stigma, externalized HIV Stigma, enacted stigma.ConclusionThe findings indicate that most interventions demonstrate varying degrees of effectiveness in reducing HIV-related stigma, with CBT-based approaches potentially being more effective, although standardization and longer follow-up periods are required. However, the differences in effectiveness across different populations, intervention content, implementation forms, and follow-up durations suggest that current stigma reduction strategies for AIDS still have room for optimization.